SIRT1 protects against myocardial ischemia–reperfusion injury via activating eNOS in diabetic rats. Issue 1 (December 2015) - Ding, Mingge; Lei, Jingyi; Han, Hongcheng; Li, Weibo; Qu, Yinxian; Fu, Enqing; Fu, Feng; Wang, Xiaoming
Abstract Background Diabetic patients are more sensitive to myocardial ischemic injury than non-diabetic patients. Silent information regulator 1 (SIRT1) is a nicotinamide adenine dinucleotide-dependent histone deacetylase making the heart more resistant to ischemic injury. As SIRT1 expression is considered to be reduced in diabetic heart, we therefore hypothesized that up-regulation of SIRT1 in the diabetic heart may overcome its increased susceptibility to ischemic injury. Methods Male Sprague–Dawley rats were fed with high-fat diet and injected with streptozotocin once to induce diabetes. Diabetic rats received injections of adenoviral vectors encoding SIRT1 (Ad-SIRT1) at five myocardial sites. Four days after adenoviral injection, the rats were subjected to myocardial ischemia and reperfusion (MI/R). Outcome measures included left ventricular function, infarct size, cellular death and oxidative stress. Results Delivery of Ad-SIRT1 into the hearts of diabetic rats markedly increased SIRT1 expression. Up-regulation of SIRT1 in diabetic hearts improved cardiac function and reduced infarct size to the extent as in non-diabetic animals following MI/R, which was associated with reduced serum creatine kinase-MB, lactate dehydrogenase activities and cardiomyocyte apoptosis. Moreover, Ad-SIRT1 reduced the increase in the superoxide generation and malonaldialdehyde content and simultaneously increased the antioxidant capability. Furthermore, Ad-SIRT1 increased eNOS phosphorylation and reduced eNOS acetylation in diabetic hearts. NOS inhibitor L-NAME inhibited SIRT1-enhanced eNOS phosphorylation, and blunted SIRT1-mediated anti-apoptotic and anti-oxidative effects and cardioprotection. Conclusions Overexpression of SIRT1 reduces diabetes-exacerbated MI/R injury and oxidative stress via activating eNOS in diabetic rats. The findings suggest SIRT1 may be a promising novel therapeutic target for diabetic cardiac complications.